Research Hotspots and Trends in Music Therapy Intervention for Patients With Dementia: A Bibliometrics and Visual Analysis of Papers Published From 2010 to 2021 - Yin, Shao; Zhu, Fengya; Li, Zhao; Che, Deya; Li, Liuying; Zhang, Lu; Zhong, Yue; Luo, Biao; Wu, Xiaohan (Frontiers in Psychiatry, 2022)
Background: As a serious public health problem, dementia has placed a heavy burden on society and families. Evidence suggests that the use of music therapy as a nondrug intervention has certain advantages with respect to reducing the behavioral and psychological symptoms of dementia (BPSD) and improving the cognition and mental status of dementia patients. However, research trends and hotspots regarding music therapy intervention for dementia analysis have not been systematically studied via bibliometric analysis. Aim: This study aims to visually analyze the research trends, hotspots and frontiers of music therapy as an intervention for dementia and to summarize future research directions in this field. Methods: We searched the Web of Science Core Collection (WoSCC) for texts published between January 1, 2010, and October 31, 2021. Using Citespase 5.8. R1 and the gCLUTO Software (Version 1.0, Graphical CLUstering Toolkit, a graphical front-end for the CLUTO data clustering library developed by Rasmussen, Newman, and Karypis from the University of Minnesota), we visualized country, institution, journal, keyword co-occurrence, keyword emergence and keyword clustering. Results: A total of 217 articles from the WoSCC database were analyzed. In this research field, the annual number of publications has generally shown a slowly increasing trend, and the United States has a prominent advantage in terms of number of publications and cooperation among countries. University College London (UCL) has the most extensive influence among research institutions. Among articles, those published in the JOURNAL OF ALZHEIMER’S DISEASE were the most numerous, with 20 such articles being published, accounting for 9.22% (20/217) of the total. Comprehensive analysis of five clusters via biclustering shows that the research hotspots in this field during the past 11 years have mainly focused on the autobiographical memory, cognitive function, mental state and BPSD of dementia patients. Conclusion: This study not only analyzes research hotspots and development trends in this field but also provides suggestions for future research. Future work should pay more attention to how to develop standardized research protocols and determine unified efficacy evaluation indicators.